p-43-p-34=p-55+1

To write p-43 as a fraction with a common denominator, multiply by 44.

p-43⋅44-p-34=p-55+1

To write -p-34 as a fraction with a common denominator, multiply by 33.

p-43⋅44-p-34⋅33=p-55+1

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply p-43 and 44.

(p-4)⋅43⋅4-p-34⋅33=p-55+1

Multiply 3 by 4.

(p-4)⋅412-p-34⋅33=p-55+1

Multiply p-34 and 33.

(p-4)⋅412-(p-3)⋅34⋅3=p-55+1

Multiply 4 by 3.

(p-4)⋅412-(p-3)⋅312=p-55+1

(p-4)⋅412-(p-3)⋅312=p-55+1

Combine the numerators over the common denominator.

(p-4)⋅4-(p-3)⋅312=p-55+1

Simplify the numerator.

Apply the distributive property.

p⋅4-4⋅4-(p-3)⋅312=p-55+1

Move 4 to the left of p.

4⋅p-4⋅4-(p-3)⋅312=p-55+1

Multiply -4 by 4.

4⋅p-16-(p-3)⋅312=p-55+1

Apply the distributive property.

4p-16+(-p–3)⋅312=p-55+1

Multiply -1 by -3.

4p-16+(-p+3)⋅312=p-55+1

Apply the distributive property.

4p-16-p⋅3+3⋅312=p-55+1

Multiply 3 by -1.

4p-16-3p+3⋅312=p-55+1

Multiply 3 by 3.

4p-16-3p+912=p-55+1

Subtract 3p from 4p.

p-16+912=p-55+1

Add -16 and 9.

p-712=p-55+1

p-712=p-55+1

p-712=p-55+1

Combine into one fraction.

Write 1 as a fraction with a common denominator.

p-712=p-55+55

Combine the numerators over the common denominator.

p-712=p-5+55

p-712=p-5+55

Simplify the numerator.

Add -5 and 5.

p-712=p+05

Add p and 0.

p-712=p5

p-712=p5

p-712=p5

Subtract p5 from both sides of the equation.

p-712-p5=0

To write p-712 as a fraction with a common denominator, multiply by 55.

p-712⋅55-p5=0

To write -p5 as a fraction with a common denominator, multiply by 1212.

p-712⋅55-p5⋅1212=0

Write each expression with a common denominator of 60, by multiplying each by an appropriate factor of 1.

Multiply p-712 and 55.

(p-7)⋅512⋅5-p5⋅1212=0

Multiply 12 by 5.

(p-7)⋅560-p5⋅1212=0

Multiply p5 and 1212.

(p-7)⋅560-p⋅125⋅12=0

Multiply 5 by 12.

(p-7)⋅560-p⋅1260=0

(p-7)⋅560-p⋅1260=0

Combine the numerators over the common denominator.

(p-7)⋅5-p⋅1260=0

Simplify the numerator.

Apply the distributive property.

p⋅5-7⋅5-p⋅1260=0

Move 5 to the left of p.

5⋅p-7⋅5-p⋅1260=0

Multiply -7 by 5.

5⋅p-35-p⋅1260=0

Multiply 12 by -1.

5p-35-12p60=0

Subtract 12p from 5p.

-7p-3560=0

Factor 7 out of -7p-35.

Factor 7 out of -7p.

7(-p)-3560=0

Factor 7 out of -35.

7(-p)+7(-5)60=0

Factor 7 out of 7(-p)+7(-5).

7(-p-5)60=0

7(-p-5)60=0

7(-p-5)60=0

Factor -1 out of -p.

7(-(p)-5)60=0

Rewrite -5 as -1(5).

7(-(p)-1(5))60=0

Factor -1 out of -(p)-1(5).

7(-(p+5))60=0

Rewrite -(p+5) as -1(p+5).

7(-1(p+5))60=0

Move the negative in front of the fraction.

-7(p+5)60=0

-7(p+5)60=0

Multiply both sides of the equation by -607.

-607⋅(-7(p+5)60)=-607⋅0

Simplify -607⋅(-7(p+5)60).

Cancel the common factor of 60.

Move the leading negative in -607 into the numerator.

-607⋅(-7(p+5)60)=-607⋅0

Move the leading negative in -7(p+5)60 into the numerator.

-607⋅-7(p+5)60=-607⋅0

Factor 60 out of -60.

60(-1)7⋅-7(p+5)60=-607⋅0

Cancel the common factor.

60⋅-17⋅-7(p+5)60=-607⋅0

Rewrite the expression.

-17⋅(-7(p+5))=-607⋅0

-17⋅(-7(p+5))=-607⋅0

Cancel the common factor of 7.

Factor 7 out of -7(p+5).

-17⋅(7(-(p+5)))=-607⋅0

Cancel the common factor.

-17⋅(7(-(p+5)))=-607⋅0

Rewrite the expression.

-1⋅(-(p+5))=-607⋅0

-1⋅(-(p+5))=-607⋅0

Multiply.

Multiply -1 by -1.

1⋅(p+5)=-607⋅0

Multiply p+5 by 1.

p+5=-607⋅0

p+5=-607⋅0

p+5=-607⋅0

Multiply -607⋅0.

Multiply 0 by -1.

p+5=0(607)

Multiply 0 by 607.

p+5=0

p+5=0

p+5=0

Subtract 5 from both sides of the equation.

p=-5

Solve for p (p-4)/3-(p-3)/4=(p-5)/5+1